Sharia Banking Relations In Halal Product Assurance Policy - Hery Purwanto (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2021)
The halal product guarantee policy stipulated in Law Number 33 of 2014 aims to provide legal certainty about the halalness of a product. The policy requires that all products circulating and traded in the territory of Indonesia must be certified halal. The policy concept generally regulates the stages of the halal certification process that must be met by business actors, both large and small industry categories, and it specifically regulates how the halal production process must be carried out to meet halal standards by referring to the Product Assurance System. Halal (SJPH). This study aims to analyze the relationship of Islamic banking in the concept of halal product assurance policy in Indonesia. This research is a literature study through a normative legal approach (statute approach) with data obtained through the relevant literature, where the analysis uses a qualitative descriptive method. The findings in this study are the construction of the Halal Product Guarantee Act does not specifically regulate Islamic financial transactions, which results in halal products produced being doubtful. The relation of Islamic banking to Law Number 33 of 2014 is very relevant and needs to be incorporated into policy provisions, considering that Islamic financial transactions can be realized through financial institutions or Islamic banking.